PJMHS 2021
DOI: 10.53350/pjmhs211551112
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of intercanthal and interalar distance to intercanine distance for selection of maxillary ant. teeth

Abstract: Background: Maxillofacial region’s reference points like interpupillary distance, intercanthal distance, interalar distance and bizygomatic width can significantly contribute toward reconstruction of two-dimensional (2D) facial profiles. Aim: To find correlation between intercanthal to intercanine and interalar to intercanine distance for maxillary anterior teeth selection. Methodology: This study was conducted at de’ Montmorency College of Dentistry/ Punjab Dental Hospital, Lahore from 29-08-2013 to 28-04-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Although there was a weak but significant correlation between the intercommissural width and anterior teeth dimensions which is contradictory to this study results, there is a strong positive correlation between the parameters. 14 However, the study conducted by Kini and Angadi showed similar results with this study and established a significant positive correlation between the parameters. 15 Deogade et al in their study stated that variations in the values may occur due to different measuring techniques used and the various population groups involved in the study.…”
Section: Discussionsupporting
confidence: 87%
“…Although there was a weak but significant correlation between the intercommissural width and anterior teeth dimensions which is contradictory to this study results, there is a strong positive correlation between the parameters. 14 However, the study conducted by Kini and Angadi showed similar results with this study and established a significant positive correlation between the parameters. 15 Deogade et al in their study stated that variations in the values may occur due to different measuring techniques used and the various population groups involved in the study.…”
Section: Discussionsupporting
confidence: 87%